RETRACTED: Study of thermal characteristics of energy efficient micro channel heat sinks in advanced geometry structures and configurations: A review - Zabdur Rehman; Faraz Ahmad; Hafiz Ali Muhammad; Fahid Riaz; Hafiz Muhammad Uzair Ayub; Mudassir Hasan; Moonyong Lee (Frontiers in Energy Research, 2022)
The sustainability and economic development is intertwined with the energy consumption and conversion processes. To suffice the ever-increasing demand of energy consumption amid environmental concerns, energy conservation and recovery along with the harnessing of renewable energy has been mandated by the policy regulators. In any energy conversion process, heat exchangers are vital operation component and has been part of any energy conversion process since the Nineteenth century. However, due to the increased energy demand, requirement of high efficiency and space and material constraints, the need for miniaturized light-weight heat exchangers with adequate heat transfer characteristics persists. Traditional heat exchangers are outdated because of its large space requirements and comparatively less heat removal rate. The miniaturized micro channel heat sink (MCHS) with tubes of about less than 1 mm have a tremendous potential to further enhance the heat transfer performance. However, its simple design doesn’t cope with the modern requirements of heat removal. Therefore, many researchers have tried to improve its performance using different techniques. The present study reviews some of the most important techniques applied to MCHS. These techniques include, coolant types used in MCHS, MCHS shapes, flow conditions, numerical methods used for this research, and materials used to manufacture MCHS. Moreover, some recommendations have been given to provide opportunities to researchers for future aspects.